The influence of cadmium on hepatic protein synthesis in the rat - Norton, Kathleen Barbara (Division of Chemical Pathology, 2020)
Cadmium is a metallic element which is placed between Zn and Hg in Group I IB of the Periodic Table. It is divalent, as are the Group I IA elements Ca and Mg. In order of electropotential, Zn, Cd and Hg fal I below Ca and Mg but above the transition elements, with which they do not have close relationships. They have low melting points so their volatility, as in the case of Pb, is an industrial hazard. Cd has recently received prominence as a cause of environment pollution due to its accumulation in water supplies and crops from Zn mining operations and industrial effluents.